Chemical composition of the leaf oil of Peperomia hernandiifolia (Piperaceae) from Costa Rica - Cicció, José (Lankesteriana: International Journal on Orchidology, 2015)
The composition of the essential oil from leaves of Peperomia hernandiifolia (Piperaceae) from Costa Rica was analyzed by capillary GC/MS. Eight compounds were identified corresponding to about 99% of the oil. The oil was constituted almost exclusively by fatty acid derivatives. The mayor components were decanal (85.0%) and decanoic acid (12.6%).